Curcumin Blocks High Glucose-Induced Podocyte Injury via RIPK3-Dependent Pathway - Chung, Hyunsoo; Lee, Seong-Woo; Hyun, Miri; Kim, So Young; Cho, Hyeon Gyu; Lee, Eun Soo; Kang, Jeong Suk; Chung, Choon Hee; Lee, Eun Young (Frontiers in Cell and Developmental Biology, 2022)
Podocyte loss is well known to play a critical role in the early progression of diabetic nephropathy, and a growing number of studies is paying attention to necroptosis, a programmed cell necrosis, to be its mechanism. Although necroptosis is a recently established concept, the significance of receptor interacting serine/threonine kinase 3 (RIPK3), a gene that encodes for the homonymous enzyme responsible for the progression of necroptosis, is well-studied. Curcumin, a natural hydrophobic polyphenol compound responsible for the yellow color in Curcuma longa, has drawn attentions with its antioxidative and anti-inflammatory properties on cells prone to necroptosis. Nonetheless, there are no known effects of curcumin on high glucose-induced podocyte necroptosis. Therefore, this study observed RIPK3 expression in high glucose-treated podocytes, to identify the involvement of necroptosis via RIPK3 pathway in diabetic nephropathy, and the effects of curcumin treatment on RIPK3-dependent podocytopathy in a hyperglycemic environment. The study discovered that increased reactive oxygen species (ROS) in renal podocytes stimulated by high glucose was improved with curcumin treatment. Furthermore, curcumin treatment has significantly restored the upregulated levels of VEGF, TGF-β, and CCL2 mRNA and downregulated level of nephrin mRNA in cultured podocytes exposed to high glucose environment. High glucose-induced changes in protein expression of TGF- β, nephrin, and CCL2 were considerably reverted to the original level with curcumin treatment. When treating curcumin, increased RIPK3 protein expression was alleviated in high glucose-treated podocytes. Additional western blot analyses of high glucose-treated podocytes treated with N-acetylcysteine (NAC, an antioxidant) or GSK’872 (a RIPK3 inhibitor) showed reductions in RIPK3 expression, which corresponded to the effects of curcumin. DCF-DA assay confirmed that such a result was attributed to the reduction of RIPK3 through the antioxidant effect of curcumin. Further observations of DCF-DA sensitive intracellular ROS in NAC-treated and GSK’872-treated podocyte groups showed a reciprocal regulatory relationship between ROS and RIPK3. Thus, we concluded that curcumin treatment protects against high glucose-induced podocyte injuries by suppressing abnormal expressions of ROS, nephrin, and inflammatory cytokines – such as VEGF, TGF- β, and CCL2 – worked as a RIPK3 inhibitor.